Policy Effectiveness Program for Improving Education Equality through the Development of Education Facilities and Infrastructure - Lia Nurhayati (Journal of Education Review Provision, 2021)
In one part of the Gorontalo Province, Bone bolango since its inauguration as a Regency on February 25, 2003 with an area of 1,984.31 km, of course, has problems in terms of educational equality, difficulty access to education due to geographical conditions and inadequate road and transportation access. which results in the lack of equal distribution of education, especially education, especially basic education. There are still many areas in Bone Bolango Regency where people have not been able to enjoy education. The solution for meeting basic education needs in Bonebolango Regency begins with opening road access and transportation, so that the area is easily accessible. Over time, in every village in Bonebolango District, there are already several elementary schools that allow each community to receive an education. However, the problem of fulfilling the need for educational facilities and infrastructure is still constrained by the lack of budget available in the local government. There are still many areas in Bone Bolango Regency where people have not been able to enjoy education. The solution for meeting basic education needs in Bonebolango Regency begins with opening road access and transportation, so that the area is easily accessible. Over time, in every village in Bonebolango District, there are already several elementary schools that allow each community to receive an education. However, the problem of meeting the needs for educational facilities and infrastructure is still constrained by the lack of budget available in the Regional Government. This study used a qualitative method, describing the program policies to increase educational equity.